Prospects of development of railway transportation in the Republic of Kazakhstan in the framework of the strategy «Nurly Jol» - Nurgaliyeva, G. K. (Journal of Economic Research & Business Administration, 2016)
Development and implementation of an integrated strategy aimed at ensuring the sustainable competitiveness of the economy is the main di rection of state policy, in order to ensure successful integration of Kazakh stan into the world economy.At the turn of the new stage of socio-economic modernization of Ka zakhstan’s dynamic development and efficient operation of the transport sector is one of the key conditions for achieving high and sustainable eco nomic growth, national security and defense capability of the country and improving the living standards of the population, rational integration into the world economy and, consequently, becoming one of the 30 most com petitive countries in the world.In this regard, in the present article reveals the peculiarities of develop ment of railway transport in the Republic of Kazakhstan, analyzed patterns of transportation in recent years, formulated the strategy for the develop ment of transit transport. Also discusses the problems in the industry, rec ommendations for solving these problems.